2013
DOI: 10.1007/s10948-013-2145-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Criticality Stabilizes High T c Superconductivity Against Competing Symmetry-Breaking Instabilities

Abstract: The occurrence of high-Tc superconductivity in systems including the cuprates and the iron-based superconductors, is known to coincide with the existence of anomalous normal-state properties which have been associated with quantum criticality. We argue here that this observation results from the fact that quantum criticality can allow the occurrence of very-strong-coupling superconductivity by preventing its suppression due to competing symmetry-breaking instabilities. Treating the electrons through a large-U … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In this way, scale invariant textures have been observed in lattice, spin, and charge degrees of freedom in strongly correlated oxide perovskites [16][17][18][19][20][21] and at metal-insulator transitions [22]. These results have shown that scale invariance [23,24] in granular matter near a critical point has been favoring quantum coherence in high-temperature superconductivity [25][26][27][28][29]. Lattice complexity beyond the average crystalline structure effects in the mechanism of high Tc superconductivity at optimum doping is attracting high interest.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, scale invariant textures have been observed in lattice, spin, and charge degrees of freedom in strongly correlated oxide perovskites [16][17][18][19][20][21] and at metal-insulator transitions [22]. These results have shown that scale invariance [23,24] in granular matter near a critical point has been favoring quantum coherence in high-temperature superconductivity [25][26][27][28][29]. Lattice complexity beyond the average crystalline structure effects in the mechanism of high Tc superconductivity at optimum doping is attracting high interest.…”
Section: Introductionmentioning
confidence: 99%
“…28NiO 4 , using the combination of the resonant X-ray Scattering (RXS) and XPCS. This could provide important information on the CDW nanoscale dynamic in complex material characterized by nanoscale phase separation.The physics of complex materials and the emerging coherent macroscopic state like superconductivity is still an open problem [1,2]. In particular, the interplay between the Charge-Density-Wave (CDW), the SpinDensity-Wave (SDW) and the defects ordering is under an intense discussion [3,4].…”
mentioning
confidence: 99%